Color Distribution Differences in the Tongue in Sleep Disorder. (27th April 2014) - Jung, Chang Jin; Nam, Ji Ho; Jeon, Young Ju; Kim, Keun Ho
Abstract : Introduction . According to traditional East Asian medicine (TEAM) theory, the tongue represents conditions of qi and blood. In the present study, the relationship between the tongue and the qi and blood in conditions with no apparent disease was investigated. Methods . A total of 454 elderly people with no apparent disease were recruited. Two Korean oriental medicine doctors classified subjects into a normal group (n = 402 ) and a sleep disorder group (n = 52 ). Three to five weeks after the experiment, 153 subjects were rerecruited for a second experiment. Two-dimensional color histograms, whose seven variables represent the color distribution in Commission Internationale de l'Éclairage 1976 ( L *, a *, b *) color space, were produced from tongue images. Results . The color of the tongue body in the sleep disorder group appeared paler than that in the normal group, and the tongue coating in the normal group was less widely distributed compared with that in the sleep disorder group. The differences in tongue color between the normal at first experiment and sleep disorder at second experiment conditions were similar to the differences between the normal and the sleep disorder groups. Conclusions . The tongue states in the sleep disorder group indicate a qi and blood deficiency according to TEAM theory.